Brand Awareness : PT Nutrifood Indonesia - Afiati Lasmiandari, Fatin; Regita, Rena; Amalia, Bintang; Nurfalah, Farida; Andriany, Dian (Green Publisher Indonesia, 2024)
Brand awareness is an important aspect for all companies to be known by their target market. This is important to ensure brands can survive the increasingly fierce business competition. In the midst of the increasing number of healthy sachet drink brands that have emerged, each brand needs to show their differentiating side in order to be able to compete. This is what encourages PT Nutrifood to increase brand awareness, one of which is through an event sponsorship strategy. This research aims to find out how PT Nutrifood can increase brand awareness through sponsorship events. This study uses marketing communication mix theory and qualitative methodology with a descriptive case study research type. The data collection techniques used are observation, in-depth interviews, and documentation. In-depth interviews were conducted with four informants: key informants, first informants, second informants and third informants. This study shows that the marketing communication used by PT Nutrifood in increasing brand awareness by using several elements or communication mixes that are interrelated. The results of the study show that event sponsorship activities carried out by PT Nutrifood and its cooperation partners have succeeded in increasing brand awareness.